INSTITUTIONAL ASPECTS OF THE DEVELOPMENT OF PUBLIC–PRIVATE PARTNERSHIP AND THE PRIVATE SECTOR IN UZBEKISTAN’S HEALTHCARE SYSTEM - Otabekova, Gulbadan Otabek qizi (THE INNOVATION ECONOMY, 2026)
This article analyzes the development processes of the private sector and public–private partnership (PPP) mechanisms in the healthcare system of Uzbekistan from both theoretical and practical perspectives. The study identifies a “dual” development dynamic characterized by the coexistence of positive institutional reforms and persistent structural and institutional constraints. The paper examines the rapid growth in the number of private medical institutions, the dominant position of the private sector in several specialized medical services, and the increasing share of private providers in the inpatient care segment. At the same time, relatively low levels of public healthcare expenditure, a high share of out-of-pocket payments, the incomplete implementation of mandatory health insurance, regional disparities, and shortages of medical personnel are identified as key factors limiting the sustainable development of the sector. The findings provide a basis for formulating policy-oriented conclusions aimed at ensuring the sustainable development of the national healthcare system through the coordination of public policy, institutional reforms, and private sector activity.